Maintenance pazopanib versus placebo in Non-Small Cell Lung Cancer patients non-progressive after first line chemotherapy: A double blind randomised phase III study of the lung cancer group, EORTC 08092 (EudraCT: 2010-018566-23, NCT01208064). Issue 12 (August 2015) - O'Brien, Mary E.R.; Gaafar, Rabab; Hasan, Baktiar; Menis, Jessica; Cufer, Tanja; Popat, Sanjay; Woll, Penella J.; Surmont, Veerle; Georgoulias, Vassilis; Montes, Ana; Blackhall, Fiona; Hennig, Ivo; et al.
Abstract Background Switch maintenance is an effective strategy in the treatment of advanced Non-Small Cell Lung Cancer (NSCLC). Pazopanib is an oral, multi-targeted tyrosine kinase inhibitor (TKI). EORTC 08092 evaluated pazopanib given as maintenance treatment following standard first line platinum-based chemotherapy in patients with advanced NSCLC. Methods Patients with non-progressive disease after 4–6 cycles of chemotherapy were randomised to receive either pazopanib 800 mg/day or matched placebo until progression or unacceptable toxicity. The primary end-point was overall survival and secondary end-points were progression-free survival (PFS) and safety. Results A total of 600 patients were planned to be randomised. The trial was prematurely stopped following an early interim analysis, after 102 patients were randomised to pazopanib (n = 50) or placebo (n = 52). Median age was 64 years in both arms. Median overall survival was 17.4 months for pazopanib and 12.3 months for placebo (adjusted hazard ratio (HR) 0.72 [95% confidence interval (CI) 0.40–1.28]; p = 0.257). Median PFS was 4.3 months versus 3.2 months (HR 0.67, [95% CI 0.43–1.03], p = 0.068). PFS rates at 4 months were 56% and 45% respectively. The majority of treatment-related adverse events (AEs) were grade 1–2. Grade 3–4 AEs (pazopanib versus placebo) were hypertension (38% versus 8%), neutropenia (8% versus 0%), and elevated SGPT (6% versus 0%). Of the patients randomised to pazopanib, 22% withdrew due to a treatment-related AE. Conclusions Switch maintenance with pazopanib following platinum-based chemotherapy in advanced NSCLC patients had limited side-effects. This study was stopped due to lack of efficacy by stringent criteria for PFS at a futility interim analysis.